A note on 'Pricing and ordering decisions in a supply chain with imperfect quality items and inspection under buyback of defective items'. Issue 15 (3rd August 2018) - Bräuer, Ina; Buscher, Udo
Abstract : Taleizadeh, Noori-daryan, and Tavakkoli-Moghaddam consider pricing and ordering decisions in a three-level supply chain with defective items and inspection processes in their paper published in 2015. They examine three scenarios for defective items at the manufacturer: disposal, rework and selling at a lower price. Unfortunately, this interesting and innovative paper suffers from some shortcomings that are addressed in our note.